23=-4m+2-3m

Simple and best practice solution for 23=-4m+2-3m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23=-4m+2-3m equation:


Simplifying
23 = -4m + 2 + -3m

Reorder the terms:
23 = 2 + -4m + -3m

Combine like terms: -4m + -3m = -7m
23 = 2 + -7m

Solving
23 = 2 + -7m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '7m' to each side of the equation.
23 + 7m = 2 + -7m + 7m

Combine like terms: -7m + 7m = 0
23 + 7m = 2 + 0
23 + 7m = 2

Add '-23' to each side of the equation.
23 + -23 + 7m = 2 + -23

Combine like terms: 23 + -23 = 0
0 + 7m = 2 + -23
7m = 2 + -23

Combine like terms: 2 + -23 = -21
7m = -21

Divide each side by '7'.
m = -3

Simplifying
m = -3

See similar equations:

| 1+4r=-15+6r | | 3x+-1=12x-64 | | 3(1/3)3 | | 5e+7e-9-e=84-4e | | (1/3)(1/3)(1/3)3=a | | 4/5y-8+=2/5+16 | | 8/2x=15/60 | | 7(k-3)= | | 2a+3b+7c= | | 3x+54y-12=0 | | 6(3-4y)= | | n+29=48 | | -4(-2b-7)=-44 | | 1.84/2.85=5.14/t | | 3i*x=y | | 2(5t-4)+6=40-t | | 49.2=1.5h | | 2(4m+1)=3 | | 114/95=95/x | | 6.4=16y | | xx/7-3=4 | | (2x-7)3=10x-9 | | -43=x/16 | | x-1=6/x | | 6x^3+56=53x-x^2 | | 7=5/6b-8 | | Y^2+3y=x | | (6+4x)*(15x+25)=0 | | F(x)=4*logx | | 3485x^2-311107.5x-18855000=0 | | n/36=17/72 | | 7w+6-3w=6 |

Equations solver categories